Ação do diclofenaco de sódio, após a interrupção da peritonite estercorácea, no cólon de ratos. Estudo da resistência mecânica e do colágeno tecidual. - Verderese, L. R.; Naresse, L. E.; Leite, C. V.; Mercadante, M. C.; Sadatsune, T.; Curi, P. R.; Burini, R. C.; Kobayasi, S. (My University, 1995)
The objective of the present study was to investigate changes in colon wall in rats with fecal peritonitis (Per) associated with sodium diclofenac (SD) by studying breaking strength and tissue collagen concentration. The rats were divided into the following experimental groups: GROUP 1-SD: 60 animals injected intramuscularly with sodium diclofenac at the dose of 2 mg/kg body weight; GROUP 2-Per: 60 animals injected intraperitoneally with a suspension of human feces. Peritonitis was interrupted after six hours of evolution; GROUP 3-Per+SD: 60 animals injected intraperitoneally with a suspension of human feces and receiving SD according to the schedule used for Groups 1 and 2; CONTROL GROUP: 12 animals injected intramuscularly with physiological saline. The animals of Group 1, 2 and 3 were successively sacrificed 2, 4, 7, 14 and 21 days after interruption of peritonitis an/or the beginning of treatment. Under conditions of the experimental model and of the methods used, we conclude that sodium diclofenac, peritonitis and the peritonitis-sodium diclofenac association decrease the breaking strength and the concentration of tissue collagen in the colon segment.
Sodium diclofenac effect, after interruption of the stercoraceous peritonitis, on the rat colon. Study of mechanical resistance and collagen concentration
Keywords: collagen; diclofenac; nonsteroid antiinflammatory agent; animal; colon; drug effect; feces; metabolism; pathophysiology; peritonitis; randomization; rat; tensile strength; Wistar rat; Animals; Anti-Inflammatory Agents, Non-Steroidal; Collagen; Colon; Diclofenac; Feces; Peritonitis; Random Allocation; Rats; Rats, Wistar; Tensile Strength